Equity implications of rice fortification: a modelling study from Nepal. Issue 15 (6th October 2020) - Saville, Naomi M; Maharjan, Macharaja; Manandhar, Dharma S; Harris-Fry, Helen A
Abstract: Objective: To model the potential impact and equity impact of fortifying rice on nutritional adequacy of different subpopulations in Nepal. Design: Using 24-h dietary recall data and a household consumption survey, we estimated: rice intakes; probability of adequacy (PA) of eight micronutrients commonly fortified in rice (vitamin A, niacin (B3 ), pyridoxine (B6 ), cobalamin (B12 ), thiamin (B1 ), folate (B9 ), Fe and Zn) plus riboflavin (B2 ), vitamin C and Ca and mean probability of adequacy (MPA) of these micronutrients. We modelled: no fortification; fortification of purchased rice, averaged across all households and in rice-buying households only. We compared adequacy increases between population subgroups. Setting: (i) Dhanusha and Mahottari districts of Nepal (24-h recall) and (ii) all agro-ecological zones of Nepal (consumption data). Participants: (i) Pregnant women ( n 128), mothers-in-law and male household heads; (ii) households ( n 4360). Results: Unfortified diets were especially inadequate in vitamins B12, A, B9, Zn and Fe. Fortification of purchased rice in rice-purchasing households increased PA > 0·9 for thiamin, niacin, B6, folate and Zn, but B12 and Fe remained inadequate even after fortification (PA range 0·3–0·9). Pregnant women's increases exceeded men's for thiamin, niacin, B6, folate and MPA; men had larger gains in vitamin A, B12 and Zn. Adequacy improved more in the hills (coefficient 0·08 (95 % CI 0·05, 0·10)) and mountains (coefficient 0·07 (95 % CI 0·01, 0·14)) but less in rural areas (coefficient −0·05 (95 % CI −0·09, −0·01)). Conclusions: Consumption of purchased fortified rice improves adequacy and gender equity of nutrient intake, especially in non-rice-growing areas.